Faktor-Faktor Yang Memengaruhi Cash Holding Pada Perusahaan Manufaktur - Clara Veda Chandra, Sofia Prima Dewi (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this study is to examine the effect of leverage, firm size, liquidity, profitability, and cash conversion cycle on cash holding. This study uses secondary data which was tested using Eviews Program 11.0. Samples that have been selected by purposive sampling method and selected as many as 51 manufacture companies as a sample from 153 companies that go public and listed on the IDX for the period 2017-2019. The results of the research showed that leverage and liquidity have positive effects to the cash holding, while firm size has no positive effect to the cash holding, profitability has no negative effect to the cash holding, and cash conversion cycle has negative effect to the cash holding.